Antioxidant effects of Citric Acid on Myocardium - Wardah Siddique, Hafiz Muhammad Imran Aziz, Sidra Mushtaq, Amina Zubair, Obaid Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Myocardial ischemia is associated with myocardial damage and necrosis. The pathogenesis of myocardial damage includes increased oxidative stress and diminished antioxidant defense. Aim: To assess levels of oxidative stress and scavenger enzyme system in experimental model of ischemia. Study design: This was a randomized experimental study. Place and duration: King Edward Medical University and University of Veterinary & Animal Sciences, Lahore for six months. Methodology: Thirty male rabbits were randomly divided into three groups. Control–group: animals got normal saline 1ml per oral for 14 days. ISO–group: animals got normal saline 1ml per oral for 14 days. CA+ISO–group: animals got citric acid 500 mg/kg body weight per oral for 14 days. Myocardial infarction was induced on 15th day in CA-group and CA+ISO-group by two doses of isoproterenol, administered subcutaneously at the interval of 24 hours. (isoproterenol dose= 85mg/kg body weight). To measure cTn-I (serum cardiac troponin I), tissue SOD (Super -oxide dismutase), CAT(catalase), GPx (glutathione peroxidase), GR (glutathione reductase), MDA (Malondialdehyde) and GSH (total reduced glutathione) animal serum was obtained from blood sample. SPSS was utilized to analyze the data. Quantitative data was shown as mean ± standard-deviation. One way analysis of variance and multiple comparison test LSD was applied. p value ≤0.05 was considered as statistically significant. Result: ISO–group showed significant decline in the level of SOD, CAT, GPx, GR and GSH as compare to control—group. ISO-group showed significant rise in the level of cTn-I and MDA. CA-group showed significantly recovery in SOD, CAT, GPx, GR and GSH levels in comparison to ISO-group. CA-group also showed significant decline in levels of cTn-I and MDA. Practical implication :Consumption of citric acid or diet rich in citric acid enhances the scavenger enzymes capability thus protects from acute myocardial infarction. Conclusion: It is concluded that citric acid possess strong anti-oxidant potential. It improves the anti-oxidant capability of myocardium in term of GSH content and level of scavenger enzymes in ischemic myocardium that help myocardium to battle against free radical injury and survive during ischemic condition. Keywords: Antioxidant, citric acid, SOD, CAT, GPx, GR, GSH